Phylogenetic approach for identification and life cycles of Puccinia (Pucciniaceae) species on Carex (Cyperaceae) from northeastern China - Ji, Jingxin; Li, Zhuang; Li, Yu; Kakishima, Makoto (Phytotaxa, 2022)
About 150 species of Puccinia on Carex (Cyperaceae) have been reported globally. However, these species can be difficult to identify due to similarities in morphology and difficulties in identifying the host plants. The presence of many cryptic species is also suspected. Based on about 130 specimens on Carex and about 40 related specimens of spermogonial and aecial stages, all collected in northeastern China, a phylogenetic approach was conducted to clarify their identification and life cycles. In the phylogenetic analyses, 17 clades among specimens on Carex were detected. Each clade was interpreted as an independent species, although many clades were morphologically similar to each other. After comparative morphology with species previously reported, seven species including three first records in China (P. circaeae-caricis, P. urticae-inflatae and P. vaginatae) were identified, while ten species (P. caricis-artemisiae, P. caricis-atractylodes, P. caricis-hebeiensis, P. caricis-jilinensis, P. caricis-lactucae, P. caricis-pediformis, P. caricis-rafaensis, P. caricis-ribicola, P. caricis-tenuiformis and P. caricis-violae) are described as new. In uredinial and telial stages, many host plant species could not be identified as they lacked an inflorescence. Thus, a phylogenetic approach is more suitable for species identifications of Puccinia on Carex rather than relying on rust morphology and host plant identification. Life cycle relations for 12 spermogonial and aecial species were also clarified using phylogenetic analyses. Furthermore, it is suspected that Puccinia species on Carex can be differentiated into species based on their spermogonial and aecial stages on the same or related host plants. Additionally, one new replacement name (P. caricis-aphanolepidis) for P. pulchella is proposed.